Impact of Yankari Game Reserve to Rural Development and Biodiversity Conservation in Yankari Communities Bauchi State - Madaki, Kanati; Umaru, Isaac John; Umaru, Kerenhapucch Isaac (Darul Yasin Al Sys, 2024)
This paper assesses the development and benefits derived by rural communities in the study area surrounding a game reserve. Questionnaires were administered to residents of fourteen selected communities within the game reserve and to the staff of the park. Additionally, focus group discussions were conducted with ten residents from each of the fourteen rural communities. A total of 720 questionnaires were distributed to residents to evaluate the development and benefits received from the establishment of the game reserve, while 250 questionnaires were distributed to the park staff to determine the impact of NGO activities on the communities. Interviews were also conducted with key stakeholders, including ward-heads, village-heads, youths, and women leaders. The findings reveal that the primary developments and benefits received by the game reserve rural communities include the establishment of primary schools, clinics, health centers, construction of roads and culverts, drilling of boreholes and wells, and access to loans for income generation. However, the relationship between farmers and pastoralists is strained, particularly during the dry season when livestock damage crops due to scarce forage. It is recommended that the working relationships between the communities and the game reserve be improved to achieve the overall objectives of conservation programs in Nigeria.